Community Empowerment through Islamic Microfinances: Perceptions in Comparison - Rifqi, Lathif Hanafir (Shirkah: Journal of Economics and Business, 2017)
BMT (Islamic saving and loan cooperative) has continuosly been one of the Islamic microfinance institutions playing a significant role in empowering economic society. There has been a number of research discussing on the effort, however none of them discussed on the perception between the empowers and the empowered group. Comparing these perceptions is a salient effort to find similarities or differencess of perceptions. This research seeks to compare empowerment perception between two organizations. One hand hand, the first party taking BMT BIF Ledok Timoho as the empowering organization and on the other hand focusing on a group of women's empowerment Ledok Timoho. Gathering data through doing observation and in-depth interview had been employed with selecting the purposive informants that contains a BMT BIF and four empowerment group representatives. To conclude, this research found that are similarities of perceptions on empowerment goals, process, outcomes and constraints.Keywords : perception, empowerment, BMT (Islamic saving and loan cooperative)